Synthesis, characterization, and determination of photophysicochemical properties of peripheral and nonperipheral tetra-7-oxy-3,4-dimethylcoumarin substituted zinc, indium phthalocyanines - ÖZDEMİR, MÜCAHİT (WILEY, 2021)
The photochemical and photophysical properties of peripheral and nonperipheral zinc and indium phthalocyanines containing 7-oxy-3,4-dimethylcoumarin synthesized were investigated in this study. 7-Hydroxy-3,4-dimethylcoumarin (1) was synthesized via Pechmann condensation reaction and then the phthalonitrile derivatives [4-(7-oxy-3,4-dimethylcoumarino)phthalonitrile (2) and 3-(7-oxy-3,4-dimethylcoumarino)phthalonitrile (3)] were synthesized by nucleophilic aromatic substitution. Phthalocyanine compounds containing coumarin units on peripheral (4and5) and nonperipheral (6and7) positions were prepared via cyclotetramerization of phthalonitrile compounds. All compounds' characterizations were performed by spectroscopic methods and elemental analysis. The phthalocyanine derivatives' (4-7) photochemical and photophysical properties were studied in DMF. The photophysical (fluorescence quantum yields and lifetimes) and photochemical (singlet oxygen and photodegradation quantum yields) properties of these novel phthalocyanines (4-7) were studied in DMF. They produced good singlet oxygen (e.g., phi(Delta)= 0.93 for7) and showed appropriate photodegradation (in the order of 10(-5)), which is very important for photodynamic therapy applications.
Keywords: coumarin; photochemical and photophysical properties; phthalocyanine; FLUORESCENT-PROBES; METAL-COMPLEXES; TETRA; BEARING; PHOTOSENSITIZERS; COPPER(II); COUMARINS; BEHAVIOR